Free radical initiation system and preparation method and application of wide voltage window high ion conductivity hydrogel polyelectrolyte
By developing a controllable/active radical initiation system, the problem of water-based zinc//lithium manganate batteries being difficult to operate stably under high voltage windows is solved, and the hydrogel polyelectrolyte with free radicals under room temperature and dark conditions is achieved, forming a wide electrochemical stable window of hydrogel polyelectrolyte, which improves the energy density and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202310394392.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-04-13
AI Technical Summary
Water-based zinc//Lithium manganate batteries are difficult to operate stably under high voltage windows, mainly because the hydrated alkali zinc sulfate layer formed on the surface of the zinc negative electrode leads to hydrogen precipitation, zinc dendrites formation and zinc corrosion. The existing radical-induced systems cannot generate free radicals under room temperature and dark conditions, and cannot form self-healing interface phases in situ.
A controlled/active radical initiation system is developed, consisting of a heated single salt solution or a solution of alkali and excess salt reaction products, capable of generating free radicals at room temperature and dark conditions, for the preparation of wide voltage windows of high ionic conductivity hydrogel polyelectrolytes.
The hydrogel polyelectrolyte that generates free radicals under room temperature and dark conditions and forms a wide electrochemical stability window can operate stably under voltage windows of 0.2-2.7V, improving the energy density and electrochemical performance of zinc// lithium manganate soft-pack batteries.
Smart Images

Figure CN116410351B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of free radical polymerization-polymer and new energy, and in particular to a controllable / active free radical initiation system and a preparation method and application of a wide voltage window high ion conductivity hydrogel polyelectrolyte. Background Art
[0002] Aqueous zinc-ion batteries have attracted widespread attention due to the advantages of zinc metal anodes such as high volume capacity, non-toxicity, and low cost. In order to obtain high energy density, aqueous zinc-ion batteries need to be able to operate at a higher voltage window. However, the narrow electrochemical stability window of aqueous electrolytes limits its possibility of operating at a high voltage window. A hydrated basic zinc sulfate layer will form on the surface of the zinc negative electrode when the battery is working, which will also lead to hydrogen evolution, zinc dendrite formation, zinc corrosion, etc. Solid electrolyte interface (SEI) is introduced to the surface of the zinc anode to broaden the working voltage range of the zinc anode and solve the above problems. However, these artificial solid interface phases will peel off from the zinc surface and form cracks during repeated zinc plating / stripping processes. The corresponding zinc / / lithium manganate battery has an operating voltage window that is difficult to exceed 2V. The cathode electrolyte interface (CEI) can ensure that the transition metal oxide positive electrode can operate stably at a high voltage window. Unfortunately, it is difficult to form CEI in aqueous zinc / / lithium manganate batteries. Even in high voltage window (2.3V) Zn / / LiMnO2 with advanced water-in-salt and deep eutectic electrolytes, CEI cannot be formed. In situ formation of SEI and CEI in aqueous Zn / / LiMnO2 batteries is essential to improve the operating voltage window.
[0003] Organic molecular electrolyte additives can contact both the positive and negative electrodes, but lack the ability to form CEI and SEI in situ at the same time. The residual monomers in the hydrogel can serve as promising electrolyte additives, polymerizing at the electrode / electrolyte interface to form SEI and CEI simultaneously. The formed polymer can also reduce the free water content at the electrode / hydrogel polyelectrolyte. For hydrogels prepared by free radical polymerization, the degree of polymerization can reach 10 within 10 seconds during chain growth. 3 -10 4. Rapid chain growth leads to residual monomers in the hydrogel. Residual monomers originate from disproportionation termination and chain transfer. For example, polyacrylamide hydrogels prepared using free radical polymerization contain residual acrylamide monomers. However, polyacrylamide hydrogels still cannot exhibit a wide electrochemical stability window, especially poor tolerance to high voltage windows. On the one hand, the LUMO and HOMO of polyacrylamide do not match the Fermi level of the electrode; on the other hand, the free radicals in the hydrogel are depleted and the initiator cannot generate free radicals at room temperature and in the dark, which results in the inability of residual monomers to form a polymer interface phase at the electrode / hydrogel interface. The current free radical initiation system cannot generate free radicals at room temperature and in the dark, and requires heating or high-energy ray irradiation to generate free radicals. This results in the inability to form a self-healing interface phase in situ at the electrode / hydrogel polyelectrolyte interface in the assembled battery. In order to broaden the wide electrochemical stability window of the hydrogel polyelectrolyte and achieve a high voltage window for the battery, it is necessary to develop a controllable / active free radical initiation system so that an interface phase is formed at the electrode / hydrogel polyelectrolyte interface in the assembled battery. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a free radical initiation system and a method for preparing and applying a hydrogel polyelectrolyte with a wide voltage window and high ionic conductivity.
[0005] According to a first aspect of an embodiment of the present application, a free radical initiation system is provided, wherein the free radical initiation system is composed of a solvent and a compound solution, wherein:
[0006] The compound solution is a heated single salt solution or a solution of a reaction product of a base and an excess salt; the anion of the salt is a chloride ion, a nitrate ion, a sulfate ion or a perchlorate ion, and the cation of the salt is an aluminum ion.
[0007] Preferably, the concentration of controllable / active free radicals generated by the free radical initiation system under heating conditions is one order of magnitude higher than that under room temperature and dark conditions.
[0008] According to a first aspect of an embodiment of the present application, a method for preparing the above-mentioned free radical initiation system is provided, comprising:
[0009] The compound solution is mixed with a solvent.
[0010] According to a third aspect of an embodiment of the present application, a method for preparing a wide voltage window high ionic conductivity hydrogel polyelectrolyte is provided, comprising:
[0011] The hydrogel polymer can be prepared by adding the required monomers to the free radical initiation system described in the first aspect and placing it at room temperature and in the dark for a predetermined time or heating it for a certain time.
[0012] Preferably, the prepared hydrogel polyelectrolyte has a wide electrochemical stability window of 3.5 V or more; the hydrogel polyelectrolyte is a single ion conductor with an ionic conductivity of 300 mS cm -1 .
[0013] Preferably, the hydrogel polyelectrolyte is a polyacrylamide hydrogel.
[0014] Preferably, the monomers for preparing the hydrogel are acrylamide and acrylic acid unsaturated monomers.
[0015] According to a fourth aspect of an embodiment of the present application, a lithium zinc manganese oxide soft-pack battery is provided, comprising: a hydrogel electrolyte, a positive electrode and a negative electrode, wherein the hydrogel electrolyte is the hydrogel electrolyte prepared according to the third aspect.
[0016] Preferably, the positive electrode and the negative electrode adopt an integrated structure of a tab current collector.
[0017] Preferably, the soft-pack battery can operate stably in a voltage window of 0.2-2.7V.
[0018] The technical solution provided by the embodiments of the present application may have the following beneficial effects:
[0019] As can be seen from the above examples, the controllable / active free radical initiation system provided by the present invention is different from the free radical formation method reported in textbooks and literature. The free radical initiation system provided by the present invention can generate free radicals under heating conditions to rapidly polymerize unsaturated monomers to form polymers. Free radicals can also be generated at room temperature and in the dark to polymerize monomers into organic matter (at this time, the free radical concentration drops by one order of magnitude).
[0020] The invention provides a method for preparing a hydrogel polyelectrolyte using a controllable / active free radical initiation system. The prepared low-concentration hydrogel has both a wide voltage window and high ionic conductivity. The zinc / / lithium manganate soft-pack battery in the third invention can operate under a high voltage window and release higher energy, laying a foundation for the commercial use of safe, environmentally friendly, and low-cost aqueous quasi-solid-state batteries.
[0021] In summary, the content of this invention will promote the further development of the field of controlled / living free radical polymerization-polymer chemistry and the commercialization of safe and low-cost energy storage in the field of new energy.
[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0024] Figure 1 1 is the electron paramagnetic resonance (EPR) spectrum of the controllable / active free radical initiation system of the embodiment of the present invention under different conditions.
[0025] Figure 2 These are the EPR images of the controllable / active free radical initiation system tested by nitrogen gas in an embodiment of the present invention under different conditions and the optical images of the prepared polyacrylamide hydrogel.
[0026] Figure 3 These are the optical pictures and corresponding EPR pictures of the hydrogel prepared by the free radical initiation system after heating at 70° C. for 48 hours in an embodiment of the present invention.
[0027] Figure 4 This is an optical picture of the free radical initiation system of an embodiment of the present invention initiating monomers to prepare polyacrylamide at room temperature and in the dark.
[0028] Figure 5 These are optical pictures of the free radical initiation system of an embodiment of the present invention heating the monomer at 70° C. for 6 hours to initiate the preparation of polyacrylamide hydrogel, an optical picture of the monomer heated at 70° C. for 6 hours, and an optical picture of the prepared polyacrylamide hydrogel immersed in an acid solution.
[0029] Figure 6 These are optical pictures of polyacrylamide hydrogel prepared by the potassium persulfate-MBA system of the embodiment of the present invention and optical pictures of polyacrylamide hydrogel prepared by the second preparation method of the controllable / active free radical initiation system.
[0030] Figure 7 1 is the linear sweep voltammetric curve of the PH and DPH polyelectrolytes of the embodiments of the present invention.
[0031] Figure 8 This is a linear sweep voltammetric curve of a polyacrylamide hydrogel polyelectrolyte prepared by the first preparation method of the controllable / active free radical initiation system of an embodiment of the present invention.
[0032] Fig. 9 It is the surface X-ray photoelectron spectrum of the titanium foil electrode of the embodiment of the present invention after measuring the cyclic voltammetry curve in PH and DPH polyelectrolytes.
[0033] Fig.10 is the freeze-dried DPH of the embodiment of the present invention 27 Al NMR spectrum.
[0034] Fig.11 and Fig.12 It is an optical picture, a structural schematic diagram, and an electrochemical performance test diagram of a zinc / / lithium manganate soft-pack battery in a 0.2-2.3V voltage window and a 0.2-2.7V voltage window. DETAILED DESCRIPTION
[0035] In order to make the purpose and technical solution of the present invention clearer, the present invention is further described in detail in conjunction with the following figures and embodiments. The specific embodiments described here are used to explain the present invention and are not used to limit the present invention.
[0036] Example 1: Preparation method of controllable / active free radical initiation system and preparation method of hydrogel.
[0037] The first preparation method of the controllable / active free radical initiation system and the preparation method of the hydrogel: add 14.40208g of aluminum sulfate to a beaker (volume 100mL) containing 30mL of deionized water, stir magnetically to completely dissolve it. Add 4g of NaOH, and use a glass rod to assist in stirring while stirring magnetically to form a white sol. Add 30mL of deionized water to form a free radical initiation system. The initiation system heats 8.68g of acrylamide monomer at 70°C (between 50-90°C) for 6 hours to prepare polyacrylamide hydrogel; or the system containing 8.68g of acrylamide monomer is left at room temperature and dark conditions for 15 days to prepare a hydrogel.
[0038] The aluminum polymer cations formed in the system will transform into each other, accompanied by the formation of free radicals. Heating will accelerate the transformation between aluminum polymer cations. Electron paramagnetic resonance spectroscopy (EPR) is used to qualitatively and quantitatively test the free radicals in the free radical initiation system, and DMPO is used as a scavenger to capture the free radicals. Figure 1 is the measured electron paramagnetic resonance spectrum data. Figure 1 (a) is the EPR of the free radical initiation system measured at room temperature and in the dark. The free radical measured is hydroxyl radical with a concentration of 1.25X10 13 / mL. Figure 1 (b)-(e) are the EPR of the free radical initiation system measured in the dark and under 70°C heating conditions. For example, the concentration of hydroxyl radicals when heated at 70°C (between 50-90°C) for 20 minutes is 3.137X10 13 / mL; the concentration of hydroxyl radicals after heating at 70℃ for 2 hours is 5.987X10 13 / mL; the concentration of hydroxyl radicals after heating at 70℃ for 6 hours is 6.313X10 13 / mL; the concentration of hydroxyl radicals after heating at 70℃ for 48 hours is 1.091X10 13 / mL. In addition, a signal similar to superoxide radicals was also detected after heating at 70℃ for 48 hours ( Figure 1(e) in the figure). As is known to all, aqueous solution contains dissolved oxygen, which will extinguish other free radicals to generate superoxide free radicals and lose their activity. Therefore, the EPR of the free radical initiation system saturated with nitrogen was tested. Figure 2 As shown in (a) of FIG. 1 , the free radical initiation system with nitrogen in the dark and at room temperature will form hydroxyl radicals with a concentration of 1.024X1013 / mL. When the system is heated at 70°C for 20 minutes, in addition to the hydroxyl radicals, sulfate radicals ( Figure 2 (b)), the total free radical concentration is 5.394X10 14 / mL. After nitrogen was introduced into the free radical initiation system containing the propionamide monomer and the air was expelled, the sealed system was heated at 70°C for 6 hours to prepare a hydrogel ( Figure 2 In order to clarify which active free radical initiating monomer is used, the EPR of the free radical initiating system saturated with nitrogen gas after heating at 70°C for 48 hours was tested ( Figure 3 (c) in Figure 1). The signals of hydroxyl radicals and superoxide radicals were detected, but the free radical initiation system failed to successfully prepare hydrogel after heating at 70°C for 48 hours. It can be concluded that the active free radical initiating the monomer is sulfate radical.
[0039] Figure 4 This is an optical picture of the controlled / active free radical initiation system containing acrylamide monomer after standing for 15 days at room temperature and in the dark. One part did not form a hydrogel. Another part formed a solid hydrogel. Figure 5 (a, b) are optical images of the hydrogel prepared by heating the free radical initiation system containing acrylamide monomer at 70°C for 6 hours. However, the aqueous solution containing only acrylamide monomer cannot be prepared into a hydrogel after heating at 70°C for 6 hours ( Figure 5 (c, d)). The low-polymer aluminum cations can be dissolved in acidic aqueous solution, which verifies the function of aluminum cations as crosslinkers. Compared with the hydrogel at the beginning of immersion ( Figure 5 (e1-e3) in the figure), the strength of the transparent hydrogel decreased significantly after being immersed in a 2 mol / L sulfuric acid aqueous solution for 7.5 hours ( Figure 5 (f1-f3) in the figure, which also verifies the function of aluminum polymer cation as a cross-linking agent.
[0040] The second preparation method of the controllable / active free radical initiation system and the preparation method of the hydrogel: The controllable / active free radical initiation system can be obtained by heating an aqueous solution containing aluminum sulfate. The controllable / active free radical initiation system can also be obtained by heating an aqueous solution containing aluminum nitrate. The controllable / active free radical initiation system can also be obtained by heating an aqueous solution of aluminum perchlorate. Dissolve acrylamide monomer (8.68g monomer-60mL deionized water) in an aqueous solution containing 0.002mol / L aluminum sulfate solution, and heat at 70°C for 6 hours to prepare a transparent polyacrylamide hydrogel ( Figure 6 (a) in the figure.
[0041] Figure 6 (a) is an optical picture of a transparent hydrogel prepared by the second preparation method and a hydrogel prepared by a potassium persulfate-N,N'-methylenebisacrylamide (MBA) system. This provides an example for directly using an aluminum sulfate aqueous solution initiation system to replace the current common potassium persulfate-MBA aqueous solution system, thus avoiding the danger of potassium persulfate explosion. In addition, a hydrogel can also be obtained by heating an aluminum nitrate aqueous solution containing a monomer ( Figure 6 (b) in the figure). Heating an aqueous solution of aluminum perchlorate containing monomers can also produce a hydrogel ( Figure 6 This further provides better support for replacing the current potassium persulfate-MBA aqueous solution system. Figure 6 The concentration of aluminum salt used is adjusted to obtain the desired hydrogel.
[0042] Example 2: Preparation method of a hydrogel polyelectrolyte (DPH) with a wide electrochemical stability window and high ionic conductivity. The first preparation method of the free radical initiation system in Example 1 was selected to prepare the hydrogel polyelectrolyte. Initiator potassium persulfate (52 mg) / crosslinker MBA (5.2 mg) was added to the selected free radical initiation system, and 8.68 g of acrylamide monomer was added at the same time to form a uniform solution. After heating at 70°C for 6 hours, a double crosslinked / double initiated polyacrylamide hydrogel (DPH) was obtained. In addition, a hydrogel prepared using the currently mature persulfate-MBA system was used as a comparative sample (PH).
[0043] Figure 7 PH and DPH linear sweep voltammetry curves. Compared with the linear sweep voltammetry curve and ionic conductivity of PH, DPH exhibits a wider electrochemical stability range and higher ionic conductivity. In addition, the linear sweep voltammetry curve ( Figure 8). Compared with the linear sweep voltammetric curve and ionic conductivity of PAAmH(PH) polyelectrolyte, PAAmPCH exhibits a wider electrochemical stability window and higher ionic conductivity. It can be concluded that the developed free radical initiation system can not only prepare hydrogels, but also broaden the electrochemical stability window and ionic conductivity of the prepared hydrogels.
[0044] X-ray photoelectron spectroscopy (XPS) was used to characterize the surface information of the titanium electrode after the linear sweep voltammetry test in order to observe the composition of the generated solid electrolyte. Fig. 9 This is the XPS of the titanium electrode after testing. Fig. 9 The left side of (a) is an optical picture of the titanium foil electrode after the test, and the part inserted into the hydrogel polyelectrolyte turns khaki. Fig. 9 The right side of (a) is the full XPS spectrum. Compared with the titanium foil electrode after the PH polyelectrolyte test, the surface of the titanium electrode tested in the DPH polyelectrolyte showed aluminum polymer cation signals (Al) and more polyacrylamide derivatives (increased relative content of nitrogen atoms, reduced relative content of titanium atoms). Aluminum polymer cations and polyacrylamide derivatives constitute the solid interface phase on the surface of the titanium electrode tested in DPH. The preparation of PH and DPH is based on free radical polymerization. Rapid chain growth allows the degree of polymerization of polyacrylamide to quickly reach 1000-10000, and the monomer conversion rate reaches about 95%. At the same time, disproportionation termination and chain transfer will also lead to the formation of acrylamide monomers. Therefore, the residual acrylamide monomers in the hydrogel are suitable additives that can contact the positive and negative electrode surfaces at the same time. The PH prepared using potassium persulfate as an initiator is free radical depleted on the one hand; on the other hand, potassium persulfate can only form free radicals under heating conditions, and cannot form free radicals under dark and room temperature conditions, which results in the PH hydrogel being unable to form a dense solid interface layer on the surface of the titanium foil electrode. The hydrogel prepared by the first preparation method of the free radical initiation system in Example 1 can also slowly generate free radicals in the dark and at room temperature to initiate the polymerization of residual monomers ( Figure 4 This is also the proof of this statement), so a dense solid electrolyte interface phase composed of aluminum polymer cations and polyacrylamide derivatives will be formed on the surface of the titanium foil electrode tested in the DPH polyelectrolyte. This dense solid electrolyte can further avoid the contact between water and the titanium foil electrode and avoid water decomposition, thereby broadening the electrochemical stability window of DPH.
[0045] Even at pH containing salt solutes, the room temperature ionic conductivity is only 100 mS cm -1 Around 300mS cm, much lower than DPH -1 about. Fig.10 This is the freeze-dried DPH sample 27Al NMR spectrum. The aluminum polymer cations that can be detected in DPH are aluminum monomers [Al(OH2)5SO4] + 、Aluminum tetramer [Al4(OH)6(OH2) 12 ] 6+ 、Aluminum tridecamer [AlO4Al 12 (OH) 24 (OH2) 12 ] 7+ . Aluminum ions are Lewis acids that can complex Lewis bases and water molecules. Aluminum monomers, tetramers, and tridecamers in DPH are cross-linked with the nitrogen in the amide group, and the anions in DPH are almost fixed to form a single sodium ion conductor. At this time, the cationic sodium ions are subject to a smaller Coulomb force and can move quickly, showing a higher room temperature ionic conductivity. The sulfate ions in PH cannot combine with the amide group and move freely, resulting in the sodium ions being subject to a stronger Coulomb force and showing a low ionic conductivity.
[0046] Example 3: Preparation method and electrochemical performance of zinc / / lithium manganese oxide soft-pack batteries with high energy density (high operating voltage window). Fig.11 (a) is the prepared large-area DPH (CZnMn) polyelectrolyte containing zinc ions and sodium ions. Fig.11 (b) in the figure is an optical image of the prepared zinc / / lithium manganese oxide soft-pack battery. Fig.12 (a) is a schematic diagram of the structure of a zinc / / lithium manganese oxide soft pack battery. The negative electrode current collector and the tab are both zinc foil (thickness 30-200μm); the positive electrode current collector and the tab are titanium foil (thickness 50μm), and the active material lithium manganese oxide is coated on the surface of the hydrophobic carbon cloth (using the traditional scraping method). DPH (CZnMn) has the functions of both electrolyte and diaphragm. The battery cell is encapsulated with aluminum-plastic packaging materials. First, the electrochemical performance of the zinc / / lithium manganese oxide soft pack battery in the range of 0.2-2.3V was tested. Fig.11 (c) in the figure is the charge and discharge curve of the zinc / / lithium manganese oxide soft pack battery in the range of 0.2-2.3V. Fig.12 (b) is the corresponding rate graph. The discharge capacity at 0.11C can reach 410mAh / g, and the corresponding energy density can reach 471Wh / kg. It also shows excellent rate performance. Fig.11 (d) in the figure is the cycle stability test curve of the zinc / / lithium manganese oxide soft-pack battery in the range of 0.2-2.3V, which shows excellent cycle stability at a low rate of 0.35C. Fig.11(e) is the Nengquist curve of the soft pack battery before and after cycling at a rate of 0.35C in the range of 0.2-2.3V. After cycling, obvious electrode interface phase resistance appeared. In addition, the electrochemical performance of the zinc / / lithium manganate soft pack battery loaded with lithium permanganate was also tested in the range of 0.2-2.7V. Fig.12 (c) and (d) are the charge-discharge curve and rate curve, respectively, showing high specific capacity and excellent rate performance. Fig.12 (e) in the figure is the cycling stability of zinc / / lithium manganate soft-pack battery loaded with lithium permanganate in the range of 0.2-2.7V, which shows excellent cycling stability.
[0047] Those skilled in the art will readily appreciate other embodiments of the present application after considering the description and practicing the contents disclosed herein. The present application is intended to cover any modification, use or adaptation of the present application, which follows the general principles of the present application and includes common knowledge or customary techniques in the art that are not disclosed in the present application. The description and examples are intended to be exemplary only, and the true scope and spirit of the present application are indicated by the claims.
[0048] It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. Application as a free radical initiation system, characterized in that: The free radical initiation system consists of a solvent and a compound, wherein: The compound is a single salt after the solution is heated, or a reaction product of a base and an excess salt; the anion of the salt is a chloride ion, a nitrate ion, a sulfate ion or a perchlorate ion, and the cation of the salt is an aluminum ion; The free radical initiation system generates controlled / active free radicals under heating conditions at a concentration one order of magnitude higher than that under room temperature and dark conditions.
2. A method for preparing a wide voltage window high ionic conductivity hydrogel polyelectrolyte, characterized in that: include: The required monomers are added to the free radical initiation system described in claim 1, and placed at room temperature and in the dark for 15 days or heated at 70 degrees Celsius for 6 hours to prepare a hydrogel polyelectrolyte; the monomers for preparing the hydrogel are acrylamide and acrylic acid unsaturated monomers.
3. The method for preparing a wide voltage window high ionic conductivity hydrogel polyelectrolyte according to claim 2, characterized in that: The prepared hydrogel polyelectrolyte has a wide electrochemical stability window of more than 3.5V; the hydrogel polyelectrolyte is a single ion conductor with an ion conductivity of 300mS cm -1 .
4. The method for preparing a wide voltage window high ionic conductivity hydrogel polyelectrolyte according to claim 2, characterized in that: The hydrogel polyelectrolyte is polyacrylamide hydrogel.
5. Lithium zinc manganese oxide soft pack battery, characterized in that: include: A hydrogel polyelectrolyte, a positive electrode and a negative electrode, wherein the hydrogel polyelectrolyte is the hydrogel polyelectrolyte prepared according to claim 2.
6. The lithium zinc manganese oxide soft pack battery according to claim 5, characterized in that: The positive electrode and the negative electrode adopt an integrated structure of a tab current collector.
7. The lithium zinc manganese oxide soft pack battery according to claim 5, characterized in that: The lithium zinc manganese oxide soft pack battery operates stably in a voltage window of 0.2-2.7V.
Citation Information
Patent Citations
Alum-based hydrogel, preparation method thereof and application of alum-based hydrogel in energy storage
CN113955786A